Exploring The Reason of University Students to use Social Media for English Learning - Riska Ayu Pratiwi; I Putu Indra Kusuma; I Ketut Trika Adi Ana (Universitas Pendidikan Ganesha, 2024)
Numerous studies had explored the use of social media in English language learning. Those study showed that social media gave lots of benefits to both learners and educators. However, this media also brought some shortcoming even challenges for them. Nevertheless, the previous studies did not present the reason why their participants decided to keep using social media to learn English. There was just few information presented about why social media were still used in English learning either in formal or informal context of learning. Therefore, this study was conducted in an educational state university in Indonesia in order to explore the reasons of university students as English learner decided to keep using social media for learning English despite the existence of disadvantages and challenges on this media. This study was done through basic qualitative approach. By involving seven English Language Education (ELE) students, researcher conducted a semi-structured interview to collect all the data needed. An inductive theoretical analysis method was used to analyze all data. Then, the result showed that the reasons of university students decided to continue using social media in English language learning included intrinsic factors such as personal motivation and extrinsic factors such as technological advancement.